Leveraging Artificial Intelligence and Big Data: A Comprehensive Examination of Workforce Performance Enhancement, Fraud Detection in the Petroleum and Banking Sectors, Healthcare Innovations, and Ethical Considerations in Information Management Systems - Alexandra Harry; Ali Khan (BULLET : Jurnal Multidisiplin Ilmu, 2024)
In a time of swift technology development and growing data quantities, businesses in a variety of industries are realizing how important it is to boost employee performance, increase operational efficiency, and prevent fraud. The impact of employee training and development on productivity, the use of Block chain and artificial intelligence (AI) in healthcare, the application of successful fraud detection techniques in the banking and petroleum industries, and the optimization of SQL databases for big data workloads are the four main topics covered in this thorough analysis. The results highlight how crucial it is to fund staff training initiatives designed to develop competencies and promote an environment of lifelong learning in order to propel organizational success. The combination of Block chain technology with artificial intelligence (AI) has the potential to revolutionize patient-centered care and secure data management in the healthcare industry, improving both operational efficiency and health outcomes. Advanced technologies like machine learning and big data analytics, which offer strong defenses against the growing threat of fraudulent activities, are becoming more and more important in the banking and petroleum industries for detecting fraud. Effective management of big data workloads requires optimizing SQL databases using strategies like indexing, partitioning, and in-memory processing, which guarantees quick access to crucial insights. All of these observations demonstrate how training, technology, and operational strategies are intertwined in negotiating the intricacies of the modern business environment. In addition to strengthening their resilience, organizations that take proactive measures to address these issues will set themselves up for long-term growth and innovation in a setting that is becoming more and more competitive.